Psychiatric disorders and associated risk factors in a sample of adolescents in Gaborone, Botswana: a cross-sectional study - Anthony A. Olashore; Wendy Brooks; Hlanganiso Roy; Fatai Adewole Adebayo; Bonginkosi Chiliza (BMC, 2022)
Abstract Background Despite the high proportion of adolescents living with mental health issues in low- to middle-income countries (LMICs), especially in Botswana, there is a significant deficit of local research to guide an increase in prevention and treatment. We, therefore, aimed to assess the prevalence and associated risk factors of psychiatric disorders (PD) in a sample of secondary school students in Botswana. Methods This cross-sectional study included 750 students from the 13 public secondary schools in Gaborone using a multi-stage sampling technique. The Mini-International Neuropsychiatric Interview for Children and Adolescents (MINI-KID) was used to screen for PDs. Results The participant's mean age was 15.26 and SD 1.57 years, with 53.6% being female. Approximately 34% had a PD, with depression being the commonest, of whom 35% were neither receiving treatment nor aware of the available services. Perinatal complications (AOR = 4.29; 95%CI: 1.04-17.70), a family history of mental illness (AOR = 2.19; 95%CI: 1.17-4.11) and substance-related problems (AOR = 1.80; 95% CI:1.22-2.65) predicted the likelihood of developing PD. Conclusions Our findings revealed that adolescents in Botswana have many mental health issues which may affect their developmental phases. A multi-sectoral collaboration is needed for the timely detection of identified risk factors and initiation of the necessary prevention and treatment measures.